Seroprevalence and burden of hepatitis E viral infection among pregnant women in central Nigeria attending antenatal clinic at a Federal Medical Centre in Central Nigeria - Philomena Ehi Airiohuodion; Philomena Ehi Airiohuodion; Anh Wartel; Andrew B. Yako; Peter Asaga Mac; Peter Asaga Mac (Frontiers in Medicine, 2022)
IntroductionHEV infection may be life threatening in pregnant women and has been linked with 20–30% mortality, especially in the third trimester of pregnancy. HEV infection leads to elevated levels of preterm labour and other immunological parameters. It is vertically transmitted and could lead to poor feto-maternal outcomes. especially in fulminating viral hepatitis where both the mother and foetus could be lost. There is currently no known treatment or vaccine for HEV. There is therefore a need to study HEV seroprevalence and burden among vulnerable groups, such as pregnant women and their newborns in Nigeria, where maternal mortality is highly significant.MethodsA total of 200 samples were collected from pregnant women attending antenatal clinic at Federal Medical Centre (FMC) Keffi, in central Nigeria, of which (156/200) samples were from HIV-negative pregnant women and (44/200) were from HIV-positive pregnant women, using a simple random sampling method.ResultsIn total, 200 pregnant women [78.0% (156/200) HIV-negative pregnant women and 22.0% (44/200) HIV-positive pregnant women] were recruited for this study. The ages of the pregnant women ranged from 15-49 years, with a mean age of 26.4 years (± 6.23). The overall HEV IgG seropositivity in the study population was 31.5% (63/200); 95% CI (30-33).ConclusionThis study highlighted an unexpectedly high seroprevalence of HEV and poor feto-maternal outcomes in pregnant women residing in a rural and urban setting of central Nigeria. The study showed that the inherently high HEV seropositivity and poor feto-maternal outcomes may not be attributed to HEV viral hepatitis only but may be a combination of extrinsic and intrinsic factors.